Innovation in food retailing in Poland – the state of the art and future prospects - Sebastian BRAŃKA (Communications of International Proceedings, 2024)
The problem of innovation in food retailing was chosen for this study, as food retailing is a branch of retailing that satisfies elementary and everyday needs of every citizen. The contemporary scientific literature on innovations in retailing focuses more on the non-food retailing and e-commerce. Therefore it is important to highlight the various types of innovation implemented by the biggest food retailing chains. In methodological terms, the paper connects a descriptive literature review focused on innovation in retailing with a case study of the biggest Polish food retailing chains. In the paper the author identifies that the largest chains in the Polish food retail market have been implementing innovation in all the fields identified by the academia.
Keywords: Food retailing; innovation; chains